Desarrollo de una aplicación y material de multimedia (audiovisual) para el aprendizaje básico de los niños con discapacidad intelectual de la escuela de educación especial azucena Chiang de Orellana, ubicada en la provincia de Los Ríos - Bustillos Quinto, Génesis Jazmín (2019)
The proposed research is basically important because it aims to analyze the different methods used by the teacher in the learning of children with intellectual disabilities, in this way a basic learning application will be carried out, where the teacher will use it as a reinforcement in the process of teaching in children, the interest is to encourage teachers to use applications as one more method of teaching and an educational tool that could facilitate children's learning by interacting with the subject raised in the application. On the other hand, the teacher plays a very important role in guiding the child in the use of the learning application, that is, the teacher will be able to expand its range of resources, didactic strategies and education modalities that could facilitate the quality of teaching in the children of basic education. Keywords: Intellectual disability, Basic learning, Basic education, Education-learning, Special education.